Contribution of Port, Offshore, and Marine Energy Projects to Economic Growth - Marsa; Sri Alfika Nur (Professorline, 2026)
This journal examines the strategic contribution of port infrastructure, offshore engineering, and marine renewable energy projects to economic growth and sustainable development through an interdisciplinary analytical framework. It evaluates their roles in expanding trade, generating employment, fostering industrial clusters, advancing technological innovation, and strengthening national energy resilience. The study finds that modern ports enhance logistics efficiency, reduce transportation costs, increase export capacity, and attract foreign direct investment, while also stimulating supporting industries such as warehousing, shipbuilding, and digital logistics services. Offshore engineering projects including oil and gas platforms, subsea pipelines, and offshore wind installations create high skilled employment, encourage technology transfer, and strengthen domestic manufacturing and marine construction sectors. Meanwhile, marine renewable energy such as offshore wind, tidal, and wave power supports low carbon economic transitions, promotes energy diversification, and expands electricity access in remote coastal and island regions. Collectively, the integration of these maritime sectors accelerates GDP growth, strengthens regional connectivity, enhances coastal industrialization, and improves long-term economic competitiveness, particularly in coastal and archipelagic nations, positioning maritime development as a central pillar of sustainable blue economy expansion.